2021
DOI: 10.3390/antibiotics10080982
|View full text |Cite
|
Sign up to set email alerts
|

MALDI-TOF Mass Spectrometry Technology as a Tool for the Rapid Diagnosis of Antimicrobial Resistance in Bacteria

Abstract: Species identification by using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) is a routine diagnostic process for infectious diseases in current clinical settings. The rapid, low-cost, and simple to conduct methodology is expanding its application in clinical microbiology laboratories to diagnose the antimicrobial resistance (AMR) in microorganisms. Primarily, antimicrobial susceptibility testing is able to be carried out either by comparing the area under curve of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 81 publications
1
24
0
Order By: Relevance
“…Mass spectra are routinely generated by MALDI-TOF MS and most of the time not exploited for additional analysis beyond the sole identification of microorganisms. Even if several reports highlighted successful applications of MALDI-TOF MS for detection of bacterial AMR, by the presence of specific biomarkers (Feucherolles et al, 2019a;Oviaño and Bou, 2019;Yoon and Jeong, 2021) identified by classical statistical methods, there is still a mine of information encrypted in the mass spectra. More recently, a growing number of reports combining MALDI-TOF mass spectrometry and ML have shown promising results for clinical big data problems, such as AMR screening (Weis et al, 2020a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Mass spectra are routinely generated by MALDI-TOF MS and most of the time not exploited for additional analysis beyond the sole identification of microorganisms. Even if several reports highlighted successful applications of MALDI-TOF MS for detection of bacterial AMR, by the presence of specific biomarkers (Feucherolles et al, 2019a;Oviaño and Bou, 2019;Yoon and Jeong, 2021) identified by classical statistical methods, there is still a mine of information encrypted in the mass spectra. More recently, a growing number of reports combining MALDI-TOF mass spectrometry and ML have shown promising results for clinical big data problems, such as AMR screening (Weis et al, 2020a,b).…”
Section: Introductionmentioning
confidence: 99%
“…By using MALDI-TOF, several means exist to determine resistance or susceptibility to an antibiotic, e.g., the detection of proteins conferring resistance, the detection of a mass peak (biomarker) associated with resistance or antibiotic degradation. For reviews regarding the possibilities that MALDI-TOF offers in AST, please refer to these publications [ 59 , 60 , 61 , 62 , 63 ]. One notable advantage of the MALDI-TOF is that it could perform both identification and AST, simplifying the diagnostic workflow without the need to have separate methods.…”
Section: Phenotypic Methods For Antimicrobial Resistance Detection In S Aureusmentioning
confidence: 99%
“…Despite the progress, a current challenge of both platforms is the identification of pathogens directly from samples. In addition, another aspect that can significantly develop this technology is related to the ability to identify multiple bacteria in complex polymicrobial samples [86]. In this regard, several processing methods used for the preparation of different clinical samples, such as urine, cerebrospinal fluid, and blood, suitable for MALDI-TOF MS analysis have been proposed and are still in the process of standardization [86,87].…”
Section: Maldi-tof Mass Spectrometrymentioning
confidence: 99%
“…In addition, another aspect that can significantly develop this technology is related to the ability to identify multiple bacteria in complex polymicrobial samples [86]. In this regard, several processing methods used for the preparation of different clinical samples, such as urine, cerebrospinal fluid, and blood, suitable for MALDI-TOF MS analysis have been proposed and are still in the process of standardization [86,87]. Another critical challenge for MALDI-TOF MS in clinical microbiological diagnosis concerns the detection of antibiotic resistance [88] and the activation of drug efflux pumps [1].…”
Section: Maldi-tof Mass Spectrometrymentioning
confidence: 99%